Differential Modulation of Rhythmic Brain Activity in Healthy Adults by a T-Type Calcium Channel Blocker: An MEG Study - Walton, Kerry D.; Maillet, Emeline L.; Garcia, John; Cardozo, Timothy; Galatzer-Levy, Isaac; Llinás, Rodolfo R. (Frontiers in Human Neuroscience, 2017)
1-octanol is a therapeutic candidate for disorders involving the abnormal activation of the T-type calcium current since it blocks this current specifically. Such disorders include essential tremor and a group of neurological and psychiatric disorders resulting from thalamocortical dysrhythmia (TCD). For example, clinically, the observable phenotype in essential tremor is the tremor itself. The differential diagnostic of TCD is not based only on clinical signs and symptoms. Rather, TCD incorporates an electromagnetic biomarker, the presence of abnormal thalamocortical low frequency brain oscillations. The effect of 1-octanol on brain activity has not been tested. As a preliminary step to such a TCD study, we examined the short-term effects of a single dose of 1-octanol on resting brain activity in 32 healthy adults using magnetoencephalograpy (MEG). Visual inspection of baseline power spectra revealed that the subjects fell into those with strong low frequency activity (set 2, n=11) and those without such activity, but dominated by an alpha peak (set 1, n=22). Cross-validated linear discriminant analysis, using mean spectral density (MSD) in nine frequency bands as predictors, found overall that 82.5% of the subjects were classified as determined by visual inspection. The effect of 1-octanol on the MSD in narrow frequency bands differed between the two subject groups. In set 1 subjects the MSD increased in the 4.5-6.5Hz and 6.5-8.5Hz bands. This was consistent with a widening of the alpha peak toward lower frequencies. In the set 2 subjects the MSD decrease in the 2.5-4.5Hz and 4.5-6.5Hz bands. This decreased power is consistent with the blocking effect of 1-octanol on T-type calcium channels. The subjects reported no adverse effects of the 1-octanol. Since stronger low frequency activity is characteristic of patients with TCD, 1-octanol and other T-type calcium channel blockers are good candidates for treatment of this group of disorders following a placebo-controlled study.